THE INVESTIGATION FOCUSES ON HOW DIFFERENT RATIOS OF TRITICALE AND WHEAT FLOURS INFLUENCE THE RHEOLOGICAL CHARACTERISTICS OF DOUGH (Conferencea, 2025)
This article discusses modern trends in the development of flour baking technology and methods for utilizing triticale grain. The rheological properties of dough prepared with various ratios of triticale and wheat flours, including water absorption capacity, gluten content, and starch retrogradation, were studied. Experimental results show that a 70:30 ratio of triticale to wheat flour yields optimal results. Additionally, further research is recommended on the high protein and amino acid content of triticale flour.